E-COMMERCE DALAM SISTEM PEMBUKTIAN PERDATA - Tuti Haryanti (IAIN Ambon, 2013)
The development of today's technology makes it easy to make ends meet. But behind the ease of not a few causing problems particularly regarding the validity and completion process extremely difficult, both non-litigation especially in litigation, because the legal relationship is conducted through the virtual world without face-to-face direct (electronic transactions). Agreements that do not qualify subjective (Article 1320 BW) and there is compliance achievement, the agreement is valid, but the legal consequences, which may be requested cancellation. If not requested cancellation to the judge, the agreement remains binding on both parties (the sender and receiver). Conversely, if the objective conditions are not met then, the agreement is null and void. Evidence used in Electronic Commerce is the electronic evidence as stipulated in Law No. 11 Year 2008 on Information and Electronic Technology is an electronic document such as micro film and data storage devices. However, other evidence will still be required, if it can make the light and give confidence in the truth to the judge for an event it is not contrary to the law. Keyword: Electronic Commerce, Evidence, private law.